2011
DOI: 10.1002/eji.201040909
|View full text |Cite
|
Sign up to set email alerts
|

Functional type 1 regulatory T cells develop regardless of FOXP3 mutations in patients with IPEX syndrome

Abstract: Mutations of forkhead box p3 (FOXP3), the master gene for naturally occurring regulatory T cells (nTregs), are responsible for the impaired function of nTregs, resulting in an autoimmune disease known as the immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. The relevance of other peripheral tolerance mechanisms, such as the presence and function of type 1 regulatory T (Tr1) cells, the major adaptive IL-10-producing Treg subset, in patients with IPEX syndrome remains to be clarifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 44 publications
2
49
0
Order By: Relevance
“…Because IL-10-producing T cells do not rely on Foxp3 expression for their differentiation and function (34,35), these cells may contribute to the NRF2-mediated suppression of autoimmune responses in Sf mice, which are deficient in Foxp3. To examine this possibility, we measured the frequency of IL-10 ϩ CD4 ϩ T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Because IL-10-producing T cells do not rely on Foxp3 expression for their differentiation and function (34,35), these cells may contribute to the NRF2-mediated suppression of autoimmune responses in Sf mice, which are deficient in Foxp3. To examine this possibility, we measured the frequency of IL-10 ϩ CD4 ϩ T cells.…”
Section: Resultsmentioning
confidence: 99%
“…But it is not clear whether these autoantibodies play a pathogenic role for the development of diabetes. Studies of different animal and human models lacking with certain types of cells demonstrated that the lack of Tregs or impairment of their function lead to the development of autoimmune disease, including diabetes [24,25].…”
Section: T1d and Tregsmentioning
confidence: 99%
“…Indeed, functional Tr1 cells differentiate independently of FOXP3, thus suggesting that in favorable conditions, Tr1 cells could exert regulatory functions, which might compensate for the lack of tTreg dependent regulation especially in long-term surviving IPEX patients [62].…”
Section: Type 1 Regulatory T Cells In Ipex Patientsmentioning
confidence: 99%